Pengaruh Kompetensi Aparatur Desa, Komitmen Organisasi dan Partisipasi Masyarakat terhadap Pengelolaan Dana Desa (Studi pada Gampong Keude Lueng Putu - Bandar Baru Kabupaten Pidie Jaya) - Eddy, Kurniawan; Arief Syarifuddin, Evi; Rahmad, Rahmad (Singkite Journal, 2024)
Village fund management needs to be done professionally, transparently and accountably. For that, the ability and commitment of village officials (gampong) are needed to run it. This study aims to review the management ability from the support of competency; commitment of officials and participation of the local community. The study was conducted in Keude Lueng Putu village, Bandar Baru sub-district, Pidie Jaya district. With a quantitative associative method and analysis carried out using a path model approach. The study took a sample of 270 people as respondents. The results found, 1) Village fund management is influenced by aspects of village official competence, commitment and community participation both directly and indirectly, each with an impact of 36.89%, 47.03% and 37.21%. 2) Simultaneously, aspects of village official competence, organizational commitment and community participation contribute to village fund management by 54.8%.